2005
DOI: 10.1128/jb.187.8.2836-2845.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Synthesis of Internalin A inaroMutants ofListeria monocytogenesIndicates Posttranscriptional Control of theinlABmRNA

Abstract: Listeria monocytogenes mutants with deletions in aroA, aroB, or aroE exhibited strong posttranscriptional upregulation of internalin A (InlA) and InlB synthesis, which resulted in a more-than-10-fold increase in InlA-mediated internalization by epithelial Caco-2 cells and a 4-fold increase in InlB-mediated internalization by microvascular endothelial cells (human brain microvascular endothelial cells) compared to the wild-type strain. The increase in InlA and InlB production was not due to enhanced PrfA-and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…These findings are consistent with previous studies that have demonstrated B -dependent inlA expression in brothgrown L. monocytogenes (24,25,45). Four possible transcriptional start sites have been identified upstream of inlA, including at least one PrfA-dependent and one B -dependent site (24,31,43). The findings reported in the present study highlight the critical contributions of the B -dependent P4 inlA promoter for in vivo gastric internalin A-E-cadherin-mediated infections.…”
Section: Monocytogenessupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are consistent with previous studies that have demonstrated B -dependent inlA expression in brothgrown L. monocytogenes (24,25,45). Four possible transcriptional start sites have been identified upstream of inlA, including at least one PrfA-dependent and one B -dependent site (24,31,43). The findings reported in the present study highlight the critical contributions of the B -dependent P4 inlA promoter for in vivo gastric internalin A-E-cadherin-mediated infections.…”
Section: Monocytogenessupporting
confidence: 82%
“…(43) reported only three inlA promoters, excluding the P1 promoter described by Lignau et al (31). Thus, the inlA P4, P3, and P2 promoter designations used here are equivalent to the inlA P3, P2, and P1 promoters described by Dramsi et al (8) and Stritzker et al (43). The Ϫ35 and Ϫ10 regions of the B -dependent P4 promoter (24) are boldfaced and underlined.…”
Section: Methodsmentioning
confidence: 99%
“…This indicates that loss of genetic material is not the mechanism of the variation observed and suggests post-transcriptional events, such as differential protein stability and selective protein degradation, may regulate the expression of proteins like IglC. Importantly, regulation of translation has been implicated in the control of genes associated with virulence in several other organisms such as Pseudomonas aeruginosa, Listeria monocytogenes, and Burkholderia cenocepacia [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…These genes are apparently repressed by CcpA without HPr-Ser-P. A similar number of genes are down-regulated (greater than twofold) in the ccpA mutant (IIb) and hence activated in L. monocytogenes by CcpA in the presence of glucose; these genes encode mainly metabolic enzymes. Interestingly inlA and inlB which, like the other PrfAdependent virulence genes, are up-regulated in the hprK mutant (see below) also belong to this set of genes, suggesting that expression of the inlAB operon which is under the control of several promoters, including a PrfA-dependent one (37,57), is also affected directly or indirectly by CcpA.…”
Section: Resultsmentioning
confidence: 99%